2011
DOI: 10.1186/1687-1499-2011-11
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of depolarization and delay spread predictions using advanced ray-based modeling in indoor scenarios

Abstract: This article investigates the prediction accuracy of an advanced deterministic propagation model in terms of channel depolarization and frequency selectivity for indoor wireless propagation. In addition to specular reflection and diffraction, the developed ray tracing tool considers penetration through dielectric blocks and/or diffuse scattering mechanisms. The sensitivity and prediction accuracy analysis is based on two measurement campaigns carried out in a warehouse and an office building. It is shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…to the considered object) and in the forward half space (Tx and Rx located at opposite sides). Regarding the scattering pattern, several studies have proved that a single-lobe pattern centered on the direction of the specular reflection/transmission is often the best representation [9,11,18,19]. In summary, the power density p of DS in a generic scattering direction can be expressed in the following form [20]:…”
Section: Ray Tracing Modelmentioning
confidence: 99%
“…to the considered object) and in the forward half space (Tx and Rx located at opposite sides). Regarding the scattering pattern, several studies have proved that a single-lobe pattern centered on the direction of the specular reflection/transmission is often the best representation [9,11,18,19]. In summary, the power density p of DS in a generic scattering direction can be expressed in the following form [20]:…”
Section: Ray Tracing Modelmentioning
confidence: 99%
“…Since the total power density exhibits no exponential decay, it is not modeled with a circuit model. Likewise, the energy density for the adjacent rooms case is found by integrating (18). Following the same procedure, the total power density is as follows:…”
Section: Model For Incident Power Density For Wlan -Narrow Bandsysmentioning
confidence: 99%
“…The incident source is a LOS plane wave perpendicular to the surfaces (θ i =0), therefore the calculation of (32) leads to ρ = 1 π =0.318. Note that using a directive scattering pattern instead of a lambertian model, [18] has found that a scattering coefficient of 0.4 is the best value for an office environment. Moreover, [9] used a lambertian model and found a scattering coefficient of 0.316.…”
Section: A Determination Of the Reverberation Timementioning
confidence: 99%
“…The geometrical relationships between the incident and the reected/penetrated/diffracted rays are based on optical principle. We use the approximation that the path direction of a ray undergoing penetration is not modi ed by this interaction [4].…”
Section: A Specular Componentsmentioning
confidence: 99%
“…We extend the diffuse scattering algorithm for rough surfaces developed in [2], [4] to involve temporally correlated realizations for the single bounce scattering case. • For indoor environments the large number of diffuse propagation paths causes a high computational complexity for standard RT algorithms.…”
Section: Introductionmentioning
confidence: 99%